Hospital discharge on the first compared with the second day after a planned cesarean delivery a randomized controlled trial - Tan, P.C.; Norazilah, M.J.; Omar, S.Z. (2012)
OBJECTIVES: To compare patient satisfaction and exclusive breastfeeding rates for patients discharged from the hospital on postcesarean day 1 (next day) or day 2. METHODS: Healthy women admitted for planned cesarean delivery were randomized to day 1 or day 2 discharge. Postoperative assessment for suitability for discharge was based on defined criteria. Primary outcomes were patient satisfaction with their discharge timing assessed at 2 weeks and reported exclusive breastfeeding at 6 weeks after discharge. Analyses were based on intention-to-treat and per-protocol discharge. RESULTS: Of the 360 women randomized, results of 170 compared with 172 and 142 compared with 148 (day 1 compared with day 2) were available for intention-to-treat and per-protocol analyses, respectively. Nine women fulfilled discharge criteria but declined day 1 discharge, and 12 women allocated to day 2 discharge took their own discharge on day 1. Intention-to-treat analysis showed that satisfaction with discharge protocol was expressed by 148 of 170 (87.1) compared with 147 of 172 (85.5) (relative risk 1.1, 95 confidence interval CI 0.6-2.1, P=.75) and exclusive breastfeeding (at 6 weeks) was reported by 76 of 170 (44.7%) compared with 77 of 172 (44.9%) (relative risk 1.0 95% CI 0.7-1.5 P=.99 for day 1 compared with day 2 discharges, respectively). All secondary outcomes assessed at up to 6 weeks after discharge including unscheduled maternal or infant medical consultations, rehospitalizations, maternal antibiotic use, and maternal well-being, anxiety, and depression status, were similar. Results on per-protocol analysis were also similar. CONCLUSION: Day 1 discharge compared with day 2 discharge after a planned cesarean delivery resulted in equivalent outcomes.